Implementation Of Sports Athlete Welfare Fulfillment By The State - triyanto, Imam; Lamijan, Lamijan (Journal Research of Social Science, Economics, and Management, 2023)
An athlete who excels can bring and make the name of Indonesia proud, both locally, nationally, and internationally. So that it is appropriate to get high appreciation from the State, in this case the State is represented by the Youth and Sports Service (Dispora). This is as regulated in Article 21 of Law Number 3 of 2005 concerning the Sports System. The main issue of fulfilling welfare seems to have no end, due to very little attention from the state towards the welfare of its athletes. The athlete’s rights that must be fulfilled are contained in Article 55 paragraph 3 and Article 64 of Law Number 3 of 2005 concerning the Sports System. Thus, many related laws have regulated the issue of athlete welfare. However, there is still a lot of confusion over the welfare of athletes (athletes) despite the existence of the Law on the National Sports System.